Upaya Peningkatan Kinerja Karyawan Melalui Disiplin Kerja, Komunikasi, dan Pemberian Motivasi di PT. Tri Cahya Purnama Semarang - Alfin Muslikhun; Rosiana Ramadhon; Ika Listyawati (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2023)
The purpose of this research is to determine the influence of work discipline, communication and motivation on employee performance at Tri Cahya Purnama Semarang Company. The population in this study were all employees of Tri Cahya Purnama Semarang Company, numbering 190 people. The sample was determined using the Slovin formula and obtained 128 people. The data was processed using the SPSS version 22 application. The results of the research showed that the three independent variables (work discipline, communication and motivation) had a significant positive influence on the performance of employees Tri Cahya Purnama Semarang Company. The coefficient of determination test shows that 63% of employee performance can be influenced by work discipline, communication and motivation. Meanwhile, the remaining 37% is influenced by other variables.